Morphology and size controlled synthesis of the hierarchical structured Li1.2Mn0.54Ni0.13Co0.13O2 cathode materials for lithium ion batteries. (20th February 2019) - Li, Honglei; Ren, Yanbiao; Yang, Puheng; Jian, Zhixu; Wang, Wenxu; Xing, Yalan; Zhang, Shichao
Abstract: Rational morphology design and size control have been demonstrated an effective strategy to improve the electrochemical performance of cathode materials for lithium ion batteries. In this work, different morphologic Li-rich layered cathode materials Li1.2 Mn0.54 Ni0.13 Co0.13 O2 with hierarchical structures are conveniently synthesized through a facile solvothermal route followed by calcination treatment. The morphology and size of the as-prepared precursors are easily regulated by changing the addition of organic solvent with different viscosity and polarity. And their critical impacts on the microstructure and electrochemical property of Li-rich layered electrodes are further systematically investigated. In particular, the hierarchical structured Li1.2 Mn0.54 Ni0.13 Co0.13 O2 microspheres exhibit superior electrochemical performance and excellent cycling stability among all samples, delivering a discharge capacity of 281.9 mAh g −1 at 0.1 C with 84.8% retention after 100 cycles. A high discharge capacity of 143.0 mAh g −1 still can be achieved even at a high current density of 5 C. Besides, this work would also provide an effective and feasible strategy for the morphology controllable synthesis of high energy density oxide electrode materials for lithium ion batteries. Graphical abstract: In this work, we designed a facile morphology and size controlled solvothermal route to fabricate hierarchical structured Li-rich layered cathode materials Li1.2 Ni0.13 Co0.13 Mn0.54 O2 . The morphology and size of the as-prepared carbonate precursors were easily regulated by changing the addition of organic solvent with different viscosity and polarity. And their critical impacts on the microstructure and electrochemical property of Li-rich layered electrodes were further systematically investigated. Image 1 Highlights: Hierarchical structured Li1.2 Mn0.54 Ni0.13 Co0.13 O2 materials with different morphology have been successfully fabricated. The morphology of the as-prepared Li1.2 Ni0.13 Co0.13 Mn0.54 O2 materials has been tuned by changing the addition of organic solvent. The Li1.2 Ni0.13 Co0.13 Mn0.54 O2 microspheres exhibit the best electrochemical performance with enhanced kinetics properties.